Cosmological frames for theories with absolute parallelism - Fiorini, Franco Luis (2011)
The vierbein (tetrad) fields for closed and open Friedmann-Robertson-Walker cosmologies are hard to work out in most of the theories featuring absolute parallelism. The difficulty is traced in the fact that these theories are not invariant under local Lorentz transformations of the vierbein. We illustrate this issue in the framework of f(T) theories and Born-Infeld determinantal gravity. In particular, we show that the early Universe as described by the Born-Infeld scheme is singularity free and naturally inflationary as a consequence of the very nature of Born-Infeld gravitational action.